Increasing Public Awareness on TVET Roles as A Government Strategy for Reducing Youth Unemployment - Kirya Mateeke Moses (Pascasarjana Universitas Negeri Malang (UM), 2019)
Abstract: This paper with more focus on how public awareness of Business Technical Vocational Education and Training (BTVET) programs can improve the image and attitude of education stakeholders towards BTVET education system. Applying thematic review qualitative approach with secondary data from Ugandan government units and other international organization accessed through online internet search engines, this paper highlights TVET status, and its challenges in Uganda. The results indicate: most graduates lack appropriate skills and competence required in the labor market as well as entrepreneurship skills for job creation. With reference to Philippine’s success story, we suggest possible strategies applicable to popularize the gospel of TVET, its roles as mitigation measure towards youth unemployment and poverty among the marginalized and disadvantaged groups in the country. Key Words: public sensitization, TVET awareness, education reform, youth unemployment, Ugandan education system, Uganda BTVETAbstrak: Tulisan ini lebih fokus pada bagaimana kesadaran masyarakat terhadap program Pendidikan dan Pelatihan Kejuruan Teknik Bisnis (BTVET) dapat meningkatkan kesan dan sikap para pemangku kepentingan pendidikan terhadap sistem pendidikan BTVET. Dengan menerapkan pendekatan tinjauan tematik kualitatif dengan data sekunder dari unit pemerintah dan organisasi internasional yang diakses melalui mesin pencari online, penelitian ini menyoroti status TVET, dan tantangannya di Uganda. Hasilnya menunjukkan bahwa sebagian besar lulusan minim akan keterampilan kewirausahaan untuk penciptaan lapangan kerja. Mengacu pada kisah sukses Filipina, kami menyarankan strategi yang mungkin untuk mempopulerkan pendidikan TVET, perannya sebagai langkah mitigasi terhadap kemiskinan dan pengangguran di antara kelompok-kelompok yang terpinggirkan dan kurang beruntung di negara ini.Kata kunci: sensitisasi publik, kesadaran TVET, reformasi pendidikan, pengangguran kaum muda, sistem pendidikan Uganda, BTVET Uganda